Overexpression of Maize ZmMYB59 Gene Plays a Negative Regulatory Role in Seed Germination in Nicotiana tabacum and Oryza sativa - Zhai, Kaihui; Zhao, Guangwu; Jiang, Hongye; Sun, Caixia; Ren, Jingyu (Frontiers in Plant Science, 2020)
MYB transcription factors are involved in many biological processes, including metabolism, stress response and plant development. In our previous work, ZmMYB59 was down-regulated by deep sowing during maize seed germination. However, there are few reports on seed germination regulated by MYB proteins. In this study, to examine its functions during seed germination, Agrobacterium-mediated transformation was exploited to generate ZmMYB59 overexpression (OE) tobacco and rice. In T2 generation transgenic tobacco, germination rate, germination index, vigor index and hypocotyl length were significantly decreased by 25.0~50.9%, 34.5~54.4%, 57.5~88.3% and 21.9~31.3% compared to wild-type (WT) lines. In T2 generation transgenic rice, above corresponding parameters were notably reduced by 39.1~53.8%, 51.4~71.4%, 52.5~74.0% and 28.3~41.5%, respectively. On this basis, antioxidant capacity and endogenous hormones were determined. The activities of catalase, peroxidase, superoxide dismutase, ascorbate peroxidase of OE lines were significantly lower than those of WT, suggesting that ZmMYB59 reduced their oxidation resistance. As well, ZmMYB59 overexpression extremely inhibited the synthesis of gibberellin A1 (GA1) and cytokinin (CTK), and promoted the synthesis of abscisic acid (ABA) concurrently. Taken together, it proposed that ZmMYB59 was a negative regulator during seed germination in tobacco and rice, which also contributes to illuminate the molecular mechanisms regulated by MYB transcription factors.